Sentiment Analysis and Cross-lingual Word Embeddings for Endangered Languages - Alnajjar, Khalid; Hämäläinen, Mika (Zenodo, 2021)
A sentiment analyzer and cross-lingual word embeddings for endangered languages (e.g., Erzya, Moksha, Skolt Sami, Komi-Zyrian).